Why Sexual Assault in Intimate Relationships Must be Criminalized as Required by International Human Rights Law: A Response to the Symposium Comments. (2015) - Randall, Melanie; Venkatesh, Vasanthi
Abstract : Ending the marital rape exemption in criminal law is a demand for legal equality and autonomy for women, rights that are enshrined in international human rights law. Drawing on international human rights law as a source of authority for challenging the marital rape exception in criminal law allows feminist and other social justice organizations, within their specific national and local contexts, to seek greater state action and accountability toward ending this form of violence against women and this violation of women's human rights. In this reply, we challenge the arguments in the symposium that oppose or caution against criminalizing sexual violence in intimate relationships as a necessary legal strategy, and that refute our view that ending the marital rape exemption is required by international human rights law.